Analisis Kalimat Efektif dalam Teks Pidato pada Buku Bahasa Indonesia Kelas VIII Kurikulum Merdeka - Maissy Maula Fitriana; Desi Fatmasari; Ayu Hastutik Munadziroh; Estri Sal Sabila Asmaning Trias; Asep Purwo Yudi Utomo; Irfai Fathurohman (CV. Aksara Global, 2023)
This review dissects the ineffectualness of sentences in discourse messages in the Indonesian language book Class VIII of the Merdeka Educational program and in the Indonesian language module Topic 12 Class VI. This research analysis is approached using both theoretical and methodological approaches. The theoretical approach to analyzing effective sentences employs an analytical approach in the field of syntax, whereas the methodological approach employs a qualitative descriptive approach. This study's data were gathered through the use of note-taking and extensive reading as data collection methods. Reading the speech's text carefully and thoroughly is the initial step. Following that was to note any sentences in the speech's text that were deemed to be ineffective. The distribution method and the interactive analysis method were employed in this study's data analysis, which followed all data collection. Informal means of data presentation are used. Data can be presented informally by focusing on decomposition with common words. Tabular data presentation is also utilized for this research. Analysis results showed that sentences in speech text were ineffective due to the incompatibility of effective sentence characteristics like equivalence, parallelism, thriftiness, accuracy, coherence, and logic. The findings of this study enhance the researchers' understanding of the subject under investigation. This research can also be used by the general public to help them write good speech texts with good sentences. Keywords:,,,,.